Optimasi Situ (Sistem Informasi Tuberculosis) Berbasis Integrasi Virtual dan Augmented Reality pada Kader PKK Desa Candirejo, Kabupaten Semarang - Richa Yuswantina; Niken Dyahariesti; Ita Puji Lestari (UNIVERSITAS NGUDI WALUYO, 2022)
Based on data from the Central Statistics Agency (BPS) of Central Java Province in 2020 the average TB discovery rate per 100,000 population is around 210.76 and the percentage of successful TB detection in Central Java is only around 83.93%. Focused in Semarang Regency, the average TB detection rate per 100,000 population is around 174.99 and the percentage of successful TB detection is only around 84.65%. Various efforts to prevent tuberculosis must continue to be carried out in order to break the chain of transmission, establish a rapid diagnosis, control infection well, and effective treatment are very important in eradicating tuberculosis in the community. Â The purpose of this activity is to streamline IEC (Communication, Information and Education) on drugs and diseases to PKK (Family Welfare Empowerment) cadres regarding TB in order to avoid misuse (mis-use) and drug abuse (drug abuse) in order to achieve the expected therapeutic effect of treatment. effective and efficient. Some of the problems found include: 1) Low awareness, understanding and knowledge of the people of Semarang Regency, especially Candirejo Village about the risk of TB; 2) Boredom and laziness arise in patients in treatment; 3) Shame, low self-esteem or even depression in people with TB and their families, as well as the negative stigma of society; 4) Lack of understanding of the patient's family, and the community around the patient about the importance of support for TB sufferers; 5) awareness, interest and understanding related to healing, prevention. The solution offered in this service activity is to provide counseling, education and assistance to PKK Cadre of Candirejo Village which bridges communication with sufferers as an effort to prevent disease transmission, especially TB. The approach was carried out by means of observation, interviews, counseling, demonstrations on how to wash hands properly, and motivating residents to create a healthy home and environment.ABSTRAKBerdasarkan data dari Badan Pusat Statistik (BPS) Provinsi Jawa Tengah pada tahun 2020 rata-rata angka penemuan TBC per 100.000 penduduk yaitu sekitar 210,76 dan persentase keberhasilan penemuan TBC di Jawa Tengah hanya berkisar 83,93%. Terfokus di Kabupaten Semarang rata-rata angka penemuan TBC per 100.000 penduduk yaitu sekitar 174,99 tahun 2020 dan persentase keberhasilan penemuan TBC hanya sekitar 84,65%. Berbagai upaya pencegahan tuberculosis harus terus dilakukan agar dapat memutus rantai penularan, menegakkan diagnosis cepat, mengendalikan infeksi dengan baik, dan pengobatan yang efektif merupakan hal yang sangat penting dalam memberantas TBC di masyarakat. Tujuan dari kegiatan ini adalah meningkatkan informasi obat TBC dan pengatasannya kepada kader PKK (Pemberdayaan Kesejahteraan Keluarga) guna menghindari kesalahgunaan (miss-use) dan penyalahgunaan obat (drug abuse) demi tercapainya efek terapi pengobatan yang diharapkan secara efektif dan efisien. Beberapa permasalahan yang ditemukan diantaranya adalah: 1) Rendahnya kesadaran, pemahaman dan pengetahuan masyarakat Kabupaten Semarang utamanya Desa Candirejo tentang resiko TBC; 2)Timbul kebosanan dan malas pada Pasien dalam berobat; 3) Rasa malu, rendah diri atau bahkan depresi pada penderita TBC dan keluarganya, serta stigma negatif masyarakat; 4) Kurangnya pemahaman pihak keluarga pasien, dan masyarakat sekitar penderita tentang pentingnya dukungan kepada penderita TBC; 5) kesadaran, minat dan pemahaman terkait dengan penyembuhan, pencegahan. Solusi yang ditawarkan pada kegiatan pengabdian ini adalah memberikan penyuluhan, edukasi dan pendampingan pada Kader PKK Desa Candirejo yang menjembatani komunikasi dengan penderita sebagai upaya pencegahan penularan penyakit khususnya TBC. Pendekatan dilakukan dengan metode observasi, wawacara, penyuluhan, penyampaian informasi mengenai penyakit TBC.